(untitled) (Oratio Directa, 2020)
Persuasive communication and interpersonal skills are essential competencies for receptionists as the first point of contact for guests and as representatives of an organization’s image. This study explains the role of receptionist communication skills in developing service quality and a positive communication image. It uses a descriptive qualitative approach conducted for 20 working days in December 2019 at Hotel X in Central Jakarta. Data were collected through questionnaires, interviews, observation, and participant observation, and were examined through triangulation. The study indicates that receptionists require technical, personal, and communication skills as well as general and specialized knowledge. Neat appearance, clear and courteous information delivery, accuracy, responsibility, loyalty, and responsiveness support guest satisfaction and a positive organizational image.